FENOMENA KEKERASAN GENDER DALAM NOVEL-NOVEL KARYA DANIELLE STEEL - Sylvie Meiliana (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2016)
The study aims to describe gender violence phenomena in Danielle Steel’s novels. The data sources were his three novels entitled Malice, The Ghost, and Journey. The dataanalysis was content analysis using the interactive model consisting of data reduction,data display, and conclusion drawing. The findings are as follows. First, gender violenceincludes physical, psychological, and sexual violence. Second, the causes of violenceagainst women are: (a) gender discrimination, (b) weak law enforcement, and (c)dominance of patriarchal values.